Examining the effects of out-of-home and in-home constraints on leisure activity participation in different seasons of the year - Ahmad Termida, Nursitihazlin; Susilo, Yusak O.; Franklin, Joel P. (Springer International Publishing, 2016)
Using multi-day, multi-period travel diaries data of 56 days (four waves of two-week diaries) for 67 individuals in Stockholm, this study aims to examine the effects of out-of-home and in-home constraints (e.g. teleworking, studying at home, doing the laundry, cleaning and taking care of other household member[s]) on individuals’ day-to-day leisure activity participation decisions in four different seasons. This study also aims to explore the effects of various types of working schedules (ﬁxed, shift, partial- and full-ﬂexible) on individuals’ decisions to participate in day-to-day leisure activities. A pooled model (56 days) and wave-speciﬁc models (14 days in each wave) are estimated by using dynamic ordered Probit models. The effects of various types of working schedules are estimated by using 28 days of two waves’ data. The results show that an individual’s leisure activity participation decision is signiﬁcantly inﬂuenced by out-of-home work durations but not inﬂuenced by in-home constraints, regardless of any seasons. Individuals with shift working hours engage less in day-to-day leisure activities than other workers’ types in both spring and summer seasons. The thermal indicator signiﬁcantly affects individuals’ leisure activity participation decisions during the autumn season. Individuals exhibit routine behaviour characterized by repeated decisions in participating in day-to-day leisure activities that can last up to 14 days, regardless of any seasons.